Socioeconomic Status of Maintenance Hemodialysis Patients from a Tertiary Care Hospital in Lahore - Naseem, Azhar; Rafique, Zahid; Rehman, Hafiza Sumaira; Asrar, Asmara (Pakistan Journal of Kidney Diseases, 2021)
End stage renal disease is a huge burden for the health economies all across the world including wealthier nations. It is also a fact that the dialysis patients have in general poor economic status. This study from a large dialysis center in Lahore has looked at the socioeconomic status of the patients undergoing hemodialysis. This study represents in general the overall patient population in the dialysis units of Pakistan.